PUBLIC ADMINISTRATION FACING THE EFFECTS OFGLOBALIZATION: THE CHALLENGES OF COUNTRIES INTRANSITION - THE CASE OF KOSOVO - Lekaj, Fadil; Ramadani, Ragip (E-Journal VFU, 2024)
Globalization as a process is an inseparable part of all political, socio-economic, technological, educational, developmental developments, but also of institutions and public administration in all its segments. The public administration today is being reformed, modernized, transformed according to the contemporary trends of social development, this process which also presents significant challenges for the political system, the administration of the states at the national level, but also regional and supranational institutions and forums .This research aims to observe, describe, analyze and compare the trends of developments and challenges faced by public administration in the process of globalization, as well as to propose alternatives so that the traditional and modern concepts of public administration reform are in harmony with the changes. social universal.
Keywords: Administration; globalism; reform; challenge; public